Information needs and seeking behaviour of bank managers - Rajeev Bhaskaran Nair Santhakumari Amma (2008)
This study was conducted to determine the information needs and seeking behaviour of bank managers. The purose was to investigate the types and usage level of different information sources, preferred business information resources, importance and use of various electronic information sources by the managers.